Social Capital as a Moderator of the Relationship Between Perceived Discrimination and Alcohol and Cannabis Use Among Immigrant and Non-immigrant Adolescents in Israel - Walsh, Sophie D.; Kolobov, Tanya; Harel-Fisch, Yossi (Frontiers in Psychology, 2018)
Literature highlights the relationship between perceived discrimination and frequency and severity of alcohol and cannabis use. One mechanism for explaining this is the nature of perceived discrimination as a potentially traumatic interpersonal stressor, which can lead to the depletion of social and personal resources. Within a Recovery Capital (RC) framework, the current study explores whether the existence of social capital in the form of parental monitoring, friend and teacher support can buffer the relationship between perceived discrimination and alcohol and cannabis use among immigrant and non-immigrant adolescents, by replenishing the depleted resources. The study included a representative sample of 8,598 students in Israel, aged 11-18, from the Health Behaviors of School Aged Children (HBSC) 2013-14 data: 1503 immigrant adolescents from the Former Soviet Union [FSU] (N=955) and Ethiopia (N=548) and 7086 non-immigrants. Results confirmed that perceived discrimination was positively related to substance use; all three forms of social capital were negatively related to alcohol and cannabis use and moderated the relationship between perceived discrimination and substance use, with the exception of friend support in the case of alcohol use. When all three social capital measures were included together, the adult social capital measures were significant predictors of substance use. Results suggest that levels of social capital, especially as provided by parents and teachers, can help young people, both immigrant and majority group adolescents, to cope with perceived discrimination.